Why do lone mothers fare worse than lone fathers? Lone parenthood and welfare benefit receipt in Germany - Esther Geisler; Michaela Kreyenfeld (Comparative Population Studies (CPoS), 2019)
This article uses data from the German microcensuses of 2007 and 2012 to examine gender differences in welfare reliance among lone parents. Binary logistic regression was employed as the method of analysis. We show that the risk of welfare benefit receipt is lower among lone fathers than lone mothers. We also find that these gender differences can be partially explained by the socio-economic characteristics of lone fathers; compared to lone mothers, lone fathers are, on average, better educated and more likely to be living with older children. Gender differences decreased over time among parents who have never married, but remained constant among divorced parents. We present a discussion of our findings in light of recent policy reforms, in particular the reform of the German Maintenance Law of 2008, which curbed the ability of a divorced parent to collect support from an ex-spouse.
urn:nbn:de:bib-cpos-2019-09en9
Keywords: 300; Employment; Lone parents; Single parents; Social assistance; Welfare